2015
DOI: 10.1111/aor.12598
|View full text |Cite
|
Sign up to set email alerts
|

Free p-Cresol Alters Neutrophil Function in Dogs

Abstract: To achieve a clearer understanding of the mechanisms responsible for neutrophil dysfunction recently described in dogs with chronic renal failure (CRF), the plasma concentrations of free p-cresol in healthy dogs (n = 20) and those with CRF (n = 20) were compared. The degree of correlation was determined between plasma levels of p-cresol and markers of oxidative stress and function of neutrophils in these dogs. The effect of this compound on oxidative metabolism and apoptosis was assessed in neutrophils isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(56 reference statements)
4
6
0
1
Order By: Relevance
“…The hematological and biochemical profiles of healthy dogs were in accordance with the normal values of the species (Thrall et al, 2004), certifying the good health of these dogs. Laboratory and clinical changes observed in uremic dogs were similar to those recently described (Almeida et al, 2013b;Bosco et al, 2016) and were equivalent to stage 4, according to IRIS staging (IRIS, 2015).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The hematological and biochemical profiles of healthy dogs were in accordance with the normal values of the species (Thrall et al, 2004), certifying the good health of these dogs. Laboratory and clinical changes observed in uremic dogs were similar to those recently described (Almeida et al, 2013b;Bosco et al, 2016) and were equivalent to stage 4, according to IRIS staging (IRIS, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Although the CKD is common in dogs, few studies demonstrating the effect of uremic toxins on neutrophil function are available and to date we have found no studies on MG in this species. Recently, our research group demonstrated increased plasma concentration of p-cresol in uremic dogs and the involvement of this toxin in neutrophil oxidative metabolism inhibition and increased apoptosis (Bosco et al, 2016). Similar studies in humans generated new important contributions to guide therapies and the development of more efficient hemodialysis membranes (Hedayat et al, 2013;Nakabayashi et al, 2011).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Valores plasmáticos de TAC e TOC utilizando a mesma metodologia e equipamento são restritos a estudos experimentais com pequeno tamanho amostral (Almeida et al, 2013). Os valores de normalidade dos biomarcadores de estresse oxidativo estabelecidos no presente estudo foram similares e apresentaram menor amplitude que os descritos na literatura (Almeida et al, 2013;Bosco et al, 2016), exceto o ácido úrico. Essa diferença quanto ao valor médio de ácido úrico e o intervalo de confiança de todos os biomarcadores de estresse oxidativo reforçam a orientação de que cada laboratório deve estabelecer seus próprios valores de referência para adequada interpretação e controle de qualidade.…”
Section: Discussionunclassified